Brentuximab vedotin (SGN-35) in patients with transplant-naive relapsed/refractory Hodgkin lymphoma. Issue 10 (October 2013) - Sasse, Stephanie; Rothe, Achim; Goergen, Helen; Eichenauer, Dennis A.; Lohri, Andreas; Kreher, Stephan; Jäger, Ulrich; Bangard, Christopher; Kuhnert, Georg; Böll, Boris; von Tresckow, Bastian; Engert, Andreas
Abstract Only limited data are available on the role of brentuximab vedotin (SGN-35) in transplant-naive relapsed or refractory patients with Hodgkin lymphoma (HL). We thus retrospectively analyzed 14 patients with primary refractory or relapsed HL who were treated with brentuximab vedotin as single agent in a named patient program, who had not received prior high-dose chemotherapy (HDCT) and autologous stem cell transplant (ASCT) due to refractory disease (n = 9), comorbidity (n = 4) and unknown reasons (n = 1). Brentuximab vedotin resulted in an overall response rate of 71% (10/14) with five complete responses (CRs). Five of those patients with refractory disease and four patients with relevant comorbidity responded. Consolidating ASCT (n = 4) or allogeneic SCT (n = 1) was performed in five patients. Median progression-free survival (PFS) was 9 months and the median overall survival (OS) was not reached. These data indicate the therapeutic efficacy of brentuximab vedotin in chemotherapy-refractory transplant-naive patients with HL.